Platelets and Infection – An Emerging Role of Platelets in Viral Infection - Assinger, Alice (Frontiers in Immunology, 2014)
Platelets are anucleate blood cells that play a crucial role in the maintenance of hemostasis. While platelet activation and elevated platelet counts (thrombocytosis) are associated with increased risk of thrombotic complications, low platelet counts (thrombocytopenia) and several platelet function disorders increase the risk of bleeding. Over the last years more and more evidence has emerged that platelets and their activation state can also modulate innate and adaptive immune responses and low platelet counts have been identified as a surrogate marker for poor prognosis in septic patients. Viral infections often coincide with platelet activation. Host inflammatory responses result in the release of platelet activating mediators and a pro-oxidative and pro-coagulant environment, which favours platelet activation. However, viruses can also directly interact with platelets and megakaryocytes and modulate their function. Furthermore, platelets can be activated by viral antigen-antibody complexes and in response to some viruses B-lymphocytes also generate anti-platelet antibodies. All these processes contributing to platelet activation result in increased platelet consumption and removal and often lead to thrombocytopenia, which is frequently observed during viral infection. However, virus-induced platelet activation does not only modulate platelet count, but also shapes immune responses. Platelets and their released products have been reported to directly and indirectly suppress infection and to support virus persistence in response to certain viruses, making platelets a double-edged sword during viral infections. This review aims to summarize the current knowledge on platelet interaction with different types of viruses, the viral impact on platelet activation and platelet-mediated modulations of innate and adaptive immune responses.